Politische Migrationsmotive Türkeistämmiger in Nordrhein-Westfalen unter Mitarbeit von Muhammed Doğan - Aver, Caner (Nomos Verlagsgesellschaft mbH & Co. KG, 2021)
Over the past decade, the political developments in Turkey, and consequently the bilateral relations between Germany and Turkey, have been shaped by largely negative dynamics. Turkey's autocratisation has led not only to strained interstate relations but to a deterioration of the social climate in Germany as a country of immigration. In addition, the issues of xenophobia and racism in Germany have repeatedly been raised. It can be assumed that the interplay between perceived discrimination in Germany and Erdoğan's popularity as a self-styled 'lawyer for Turks' in Germany has resulted in greater susceptibility to populist promises and Turkish-nationalist identity-building. This empirical study examines how political views influence migration-related decisions of successor generations among people of Turkish origin in North Rhine-Westphalia who intend to (re)settle in Turkey.